2010
DOI: 10.1071/fp09265
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of two MATE genes in rye

Abstract: Abstract. Multidrug and toxic compound extrusion (MATE) proteins are widely present in bacteria, fungi, plants and mammals. Recent studies have showed that a group of plant MATE genes encodes citrate transporter, which are involved in the detoxification of aluminium or translocation of iron from the roots to the shoots. In this study, we isolated two homologous genes (ScFRDL1 and ScFRDL2) from this family in rye (Secale cereale L.). ScFRDL1 shared 94.2% identity with HvAACT1, an Al-activated citrate transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 41 publications
0
76
0
1
Order By: Relevance
“…Similarly, a legume MATE transporter, LjMATE1 (Lotus japonicus MATE1), was found to assist in the translocation of Fe from the roots to the nodules (Takanashi et al 2013). The citrate-mediated Fe translocation systems with MATE transporters in root xylem have also been reported in soybean GmFRD3a and GmFRD3b (Glycine max FRD3a and 3b) and rye ScFRDL1 (Secale cereal FRDL1) using reverse genetic approaches (Rogers et al 2009;Yokosho et al 2010), and also in barley HvAAC T1 (Hordeum vulgare aluminumactivated citrate transporter1) and wheat TaMATE1b (Triticum aestivum MATE1b) from studies of Al 3+ detoxification mechanisms (see "Al 3+ detoxification") (Fujii et al 2012;Tovkach et al 2013).…”
Section: Fe Translocationmentioning
confidence: 94%
“…Similarly, a legume MATE transporter, LjMATE1 (Lotus japonicus MATE1), was found to assist in the translocation of Fe from the roots to the nodules (Takanashi et al 2013). The citrate-mediated Fe translocation systems with MATE transporters in root xylem have also been reported in soybean GmFRD3a and GmFRD3b (Glycine max FRD3a and 3b) and rye ScFRDL1 (Secale cereal FRDL1) using reverse genetic approaches (Rogers et al 2009;Yokosho et al 2010), and also in barley HvAAC T1 (Hordeum vulgare aluminumactivated citrate transporter1) and wheat TaMATE1b (Triticum aestivum MATE1b) from studies of Al 3+ detoxification mechanisms (see "Al 3+ detoxification") (Fujii et al 2012;Tovkach et al 2013).…”
Section: Fe Translocationmentioning
confidence: 94%
“…To confirm the full-length cDNA sequence of Os Nramp5, we performed 59-and 39-RACE (Yokosho et al, 2010). Total RNA was extracted from rice (Oryza sativa) roots (cv Zhonghua 11) using an RNeasy plant mini kit (Qiagen).…”
Section: Cloning Of Full-length Os Nramp5 Cdnamentioning
confidence: 99%
“…Functional MATE homologs associated with Al tolerance were also identified in Arabidopsis (AtMATE; Liu et al, 2009), wheat (TaMATE1; Ryan et al, 2009), rye (ScFRDL2; Yokosho et al, 2010), and rice (OsFRDL4; Yokosho et al, 2011). Some of these genes are located near Al tolerance QTL, such as OsFRDL4, which co-localizes with a QTL on chromosome 1 that was detected in different studies (Yokosho et al, 2011).…”
Section: The Mate Familymentioning
confidence: 99%
“…However, Piñeros et al (2005) observed a low correlation between citrate exudation and Al tolerance in maize, suggesting that this species has other complementary mechanisms enabling them to tolerate Al. In addition to malate, citrate exudation has also been reported to contribute to Al tolerance in wheat, Arabidopsis, and rye (Ryan et al, 2009;Liu et al, 2009;Yokosho et al, 2010). In rice, citrate exudation (Yokosho et al, 2011) as well as symplastic mechanisms are likely to contribute to the extreme Al tolerance in this species ).…”
Section: Mechanisms Of Aluminum Tolerancementioning
confidence: 99%